IMPACT OF SPATIAL VARIABILITY IN MICROFABRICS ON THE THERMAL CONDUCTIVITY OF SUBIS LIMESTONE - Yin Sing, Lee (2011)
There are several facies in the Subis Limestone Formation. These include the skeletal rudstone, coral boundstone, mudstone and algal bindstone facies. The facies assemblage suggests a shallow biohermal depositional environment. Every facies is characterized by differences in fabric. This suggests also variation in the depositional environment. The resultant variation in microfabrics influences the thermal conductivity for each type of microfacies. Presence of corals, burrows, stylolites including differences in mineralogy between each facies appear to decrease the thermal conductivity values to varying extends. The mudstone facies has the highest thermal conductivity values among all other facies tested. The results of this study also suggest an inverse relationship between porosity and thermal conductivity values. This finding has some important bearing on the reservoir potential and stability of carbonates in general.